If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 19 + -6x = 10 Reorder the terms: 19 + 3x + -6x = 10 Combine like terms: 3x + -6x = -3x 19 + -3x = 10 Solving 19 + -3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -3x = 10 + -19 Combine like terms: 19 + -19 = 0 0 + -3x = 10 + -19 -3x = 10 + -19 Combine like terms: 10 + -19 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 6=c-15 | | 9(6k+9)+10(7k+7)= | | 10-5x=3x-22 | | 630/189 | | 4/5•(-2/9) | | 2(5x-3)=(2x+2) | | 5-3x=4x-23 | | 6m+3=5(m+4) | | 2(-3h+5)=-9h-17 | | 8x+4=10x+14 | | 3x-20=50x-10 | | 5x+-10=3x+12 | | 4x+5x=11x-40 | | n^2-5n-1=0 | | 54=11x-2x | | 49=4x+3x | | 17+7n=9+10n | | 4(4x-4)= | | 6w+8=12+8w | | 112=-w+214 | | 213-w=8 | | an=7*(-1)n-1 | | -3a+1=-4a+8 | | 9(x+1)-8=6x+3(1+x) | | 4410=225x | | 2(6x+3)-2(x+6)= | | 8x+6=5x-15 | | v/4.8=3 | | 5x-7+2x=3x-2+5 | | 11=2m+6-5 | | .75x+.5y=25 | | -3+11=-8v+51 |